Design and Characterization of 2.5D Nature-Inspired Infill Structures under Out-Plane Quasi-Static Loading Condition - Dara Ashok; M. V. A. Raju Bahubalendruni (Advances in Materials Science and Engineering)
The 2.5D (2.5-dimensional) structures are acquired to enhance safety and lightweight designs with better energy absorption in the aerospace and automobile sectors. Additive manufacturing (AM), which is practical to build suitable components in industrial and transportation applications, may produce these structures more efficiently. The current study aims to improve the 2.5D infilled structures mean crush force (MCF) and energy absorption capabilities. Under compression loading, the proposed novel nature-inspired 2.5D infilled structure is compared to six existing 2.5D geometries that are inspired by nature. These structures are made of cylindrical shells that are filled with various infill configurations and maintained at a consistent volume. Photopolymer resin is used as the material for the structures, which are created using a digital light processing (DLP) method under AM technology. The characterization of the constructed models was done under compressive out-plane quasi-static stress conditions. ANSYS numerical simulations have been carried out to confirm the dependability of experimental data. The impact of supporting ribs and infill designs on crushing behaviour is thoroughly discussed. Mean crush force (MCF) and specific energy absorption (SEA) under quasi-static compression loading are provided to the proposed unique nature-inspired 2.5D infilled structure to significantly boost crushing qualities, axial collapse, and energy absorption behaviours.